Group Guidance Services Based on Massenrempulu Cultural Values to Improve Student Character - Muhammad Junaedi Mahyuddin; Handayani Sura; Muliyadi Muliyadi; Musdin Muzakkir; Siti Aminah; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2022)
Character is a pattern of behavior that is shown in the form of actions. The focus of character development is the formation of students' mindsets. Strive for students to be positive, responsible, and have good morals. Massenrempulu cultural values are symbols of nobility that are passed down from generation to generation. Mutual respect, courtesy and ethics are termed mataratte. Mataratte is loving and respecting each other, and saying good things. This study aims to determine the effectiveness of massenrempulu cultural value-based group guidance on the character of SMK students. The approach used in this research is a quantitative approach. This type of experimental research, the research model used is Pre-Experimental Designs which examines the application of massenrempul cultural value-based group guidance to improve student character. The experimental design used was One-Group Pretest-Posttest Designs. The population in this study were students of class X and XI at SMK Latanro Enrekang. The sampling technique used simple random sampling. Based on the results of calculations using SPSS for windows through a paired sample t-test, there is a difference in the mean value after treatment which is higher than before being given treatment, with a value of t = 10.645 with df = 29. Price ttable at t 0.05 = 2.05 with a significant value (P) = 0.000 < α = 0.05. This means that the null hypothesis (Ho) which is "group guidance based on massenrempulu cultural values is not effective in improving student character is declared rejected. Hence, the working hypothesis (H1), namely "group guidance based on massenrempulu cultural values is effective in improving student character" is declared accepted. From the previous statement, it can be concluded that group guidance based on massenrempulu cultural values is effective in improving student character.